EFEKTIVITAS MEDIA PEMBELAJARAN BIOLOGI BERBASIS UPACARA KEAGAMAAN PANCA YADNYA - Oka, Dewa Nyoman; Sudirgayasa, I Gede (LPPM IKIP PGRI Bali, 2018)
This study aims to determine the effectiveness of biologylearning media based Panca Yadnya religious ceremony in delivering students competent in the field of biology. The research method used is quasi-experiment research method, with the design of Non-equivalent Posttest-Only Control Group Design. The experimental group was given treatment with the learning media based on based Panca Yadnya religious ceremony. The control group was given the treatment of learning media in biology texbooks. After the treatment, a post-test was conducted on each group with the same instrument. The research was conducted in the neighborhood of Kukuh Village and in the Secondary School 2 Marga. The sample in this research is the students of class VII A as the experimental class and the students of class VII B as the control class. The data collected in the form of data achievement learning science biology of students. Data were collected by written test. The data obtained are then analyzed descriptively and t-test statistic. All tests were conducted with significance of 0.05. T-test is done with the help of IBM SPSS Statistics 23. The results show that the biology learning media based Panca Yadnya religious ceremony very effective in delivering students competent in the field of biology. This conclusion is based on the significant difference in the mean score of students' achievement in biology of the experimental group that is superior to the control group students.